Atypical Behavior of Money and Credit: Evidence From Conditional Forecasts - Elena Afanasyeva (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
Great Recession 2007-2008 has revived interest to quantity aggregates (money and credit) and their role as indicators of financial instability for monetary and macroprudential policy. However, many of the previous empirical studies inspecting indicator properties used univariate methods and did not explicitly account for endogenous interactions of variables. We use a multivariate approach (Bayesian VAR) to detect periods of atypical behavior in money and credit in the US and in Euro Area. We find that atypical behavior of these variables is associated with periods of financial distress and (or) banking crises in the US. Moreover, we detect an unsustained credit boom prior to the Great Recession in both Euro Area and in the US. There is a link between this boom and the short-term interest rates in both regions: conditioning on the short-term interest rates substantially reduces the degree of atypical expansionary behavior of money and credit in 2003-2007.
Keywords: E47; E51; E32; 330